Why your data won't mix. - Halevy, Alon (New York ACM, 2005)
New tools and techniques can help ease the pain of reconciling schemas.
Keywords: Information Systems; Database Management; Logical design; Schema and subschema; Models and Principles; User/Machine Systems; Human information processing; Heterogenous database; Design; Human Factors; Management